Finite element modelling of sound transmission from outer to inner ear - Areias, Bruno (2016)
The ear is one of the most complex organs in the human body. Sound is a sequence of pressure waves, which propagates through a compressible media such as air. The pinna concentrates the sound waves into the external auditory meatus. In this canal, the sound is conducted to the tympanic membrane. The tympanic membrane transforms the pressure variations into mechanical displacements, which are then transmitted to the ossicles. The vibration of the stapes footplate creates pressure waves in the fluid inside the cochlea; these pressure waves stimulate the hair cells, generating electrical signals which are sent to the brain through the cochlear nerve, where they are decoded. In this work, a three-dimensional finite element model of the human ear is developed. The model incorporates the tympanic membrane, ossicular bones, part of temporal bone (external auditory meatus and tympanic cavity), middle ear ligaments and tendons, cochlear fluid, skin, ear cartilage, jaw and the air in external auditory meatus and tympanic cavity. Using the finite element method, the magnitude and the phase angle of the umbo and stapes footplate displacement are calculated. Two slightly different models are used: one model takes into consideration the presence of air in the external auditory meatus while the other does not. The middle ear sound transfer function is determined for a stimulus of 60 dB SPL, applied to the outer surface of the air in the external auditory meatus. The obtained results are compared with previously published data in the literature. This study highlights the importance of external auditory meatus in the sound transmission. The pressure gain is calculated for the external auditory meatus.